The effect of steroid hormones on the physical performance of boys and girls during an olympic weightlifting competition - Crewther, B.; Obminski, Z.; Cook, C. (Pediatric Exercise Science, 2016)
Purpose: To examine the steroid hormone effect on the physical performance of young athletes during an Olympic weightlifting competition. Methods: 26 boys and 26 girls were monitored across 2 weightlifting competitions. Pre- and post-competition testosterone (T), cortisol (C) and dehydroepiandrosterone-sulfate (DHEA-s) were measured in blood, with pre-event free T (FT) and the free androgen index (FAI) calculated. Body mass (BM) and weightlifting performance were recorded. Results:The boys had a larger BM, superior performance with more T, FT and a higher FAI than girls (p < .01). Although C (32%) and DHEA-s (8%) levels were elevated across competition, no sex differences in hormone reactivity were seen. In boys, DHEA-s correlated with performance (r = .46), but not after controlling for BM (r = .14). For girls, T correlated with performance (r = -0.51) after BM was controlled. Conclusion:The sex differences that emerge during puberty were observable, whereby the boys were larger and stronger with a more anabolic profile than girls. Individual DHEA-s (boys) and T (girls) levels were related to performance, but BM appeared to be acting as a mediating (boys) or suppressing (girls) variable. This adds new insight regarding the hormonal contribution to competitive performance in young athletes.